Descrição de estratégias educacionais entre estudantes de fisioterapia e deficientes físicos favorecedores de adesão - Soares, Monica da Silva Trabuco (Universidade Federal de São Carlos, 2010)
The physical disabilities impact the individual's life, affecting it in different ways. Disabled people in rehabilitation treatment brings a broad history of extinction of previously reinforced repertoire, coupled with the experience of aversive restrictive conditions, and the actual practice of intervention exposure to repetitive activities and challenging new ones that may even produce pain. Thus it is essential that professionals responsible for such intervention are able to model and maintain new behaviors that lead to the promotion of wellness and a better utilization of the potential of individuals, and thus ensure better patient compliance to treatment. Thus, it is necessary to investigate the use of educational strategies for professionals in training and possible indicators of adherence to treatment offered by them. This study had two objectives. The first was to identify the use of educational strategies by the students of physiotherapy, the second was to identify situations where the use of these strategies would be related to adherence to physical therapy or not. Participants were three dyads physiotherapy student / patient, composed of three graduate trainees in physical therapy and two adults with physical disabilities. The study was conducted with the unit of care in public health, linked to a public university in the State of São Paulo. Intervention sessions the physiotherapist were recorded in full by a camera equipment installed in the attendancing room. The interaction between the student-patient dyad was analyzed by observing instances of verbal and nonverbal behaviors emitted by the students and patients. The record of the events took place at intervals of 10 seconds of observation and 10 seconds to register. The behaviors analyzed were divided into two broad sets of categories: (1) Educational Strategies for the intervention and (2) Strategies Facilitators of Adherence. The results regarding the Educational Strategies showed that 87% of the occurrence of the same referred to the instructions, oral or demonstration of physical activities proposed. The use of educational strategies to promote change, setting performances by modeling or general information on health occurred at low frequency. The categories relating to the membership seems to indicate that the physical therapist in training issues in favor of joining behaviors (98%) focused more on an effort to maintain socially reinforcing relationship with the patient. The discussion shows that although physiotherapy students demonstrate mastery of strategies that strengthen the therapeutic relationship, we must emphasize the need to strengthen the training of occupational therapy in early learning and the establishment of educational strategies in the course of their work together the disabled, to ensure the maintenance of behavior modeling and compatible with new conditions of learning.
Description of Educational Strategies among Students of Physical Therapy and Handicap promoters of Accession
Keywords: Reabilitação; Psicologia; Saúde; Educação em saúde; Interações educativas; Adesão ao tratamento; Estudantes de fisioterapia; Deficiência física; Rehabilitation; Health education; Educational interactions; Adherence to treatment; Physiotherapy students; Physical disability; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO::EDUCACAO ESPECIAL